2017
DOI: 10.1371/journal.pone.0175465
|View full text |Cite
|
Sign up to set email alerts
|

Defective enamel and bone development in sodium-dependent citrate transporter (NaCT) Slc13a5 deficient mice

Abstract: There has been growing recognition of the essential roles of citrate in biomechanical properties of mineralized tissues, including teeth and bone. However, the sources of citrate in these tissues have not been well defined, and the contribution of citrate to the regulation of odontogenesis and osteogenesis has not been examined. Here, tooth and bone phenotypes were examined in sodium-dependent citrate transporter (NaCT) Slc13a5 deficient C57BL/6 mice at 13 and 32 weeks of age. Slc13a5 deficiency led to defecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 37 publications
4
36
0
Order By: Relevance
“…We demonstrated the expression of SLC13a5 in hMSCs, further showing that citrate-elevated ALP expression was dependent on SLC13a5. These findings have significant implications in bone stem cell biology, providing a biological mechanism underlying the reported contribution of exogenous citrate in teeth and bone showing that SLC13a5 deficiency in mice leads to impaired bone formation and defective tooth development (35). Similarly, consumption of extracellular citrate has been found in cancer cells that are known to be metabolically active to meet their high energetic and synthetic needs.…”
Section: Discussionmentioning
confidence: 88%
“…We demonstrated the expression of SLC13a5 in hMSCs, further showing that citrate-elevated ALP expression was dependent on SLC13a5. These findings have significant implications in bone stem cell biology, providing a biological mechanism underlying the reported contribution of exogenous citrate in teeth and bone showing that SLC13a5 deficiency in mice leads to impaired bone formation and defective tooth development (35). Similarly, consumption of extracellular citrate has been found in cancer cells that are known to be metabolically active to meet their high energetic and synthetic needs.…”
Section: Discussionmentioning
confidence: 88%
“…These analyses showed that the absence of NaCT in mice promotes longevity and protects from insulin resistance and adiposity 10 . Furthermore, NaCT deficiency led to defective tooth and bone development characterized by the absence of mature enamel, decreased bone mineral density and impaired bone formation 11 . In contrast to the human “knock-out” phenotype, it has not been reported that knock-out animals show evidence of epileptic activity of other neurological signs, which may be due to species differences of transporter expression or other compensatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with NaCT [INDY (−/−)]-knock out mice demonstrated that deletion of this transporter mimics aspects of dietary restriction and protects these mice against insulin resistance and adiposity 10 . Furthermore, the absence of this transporter led to defective tooth and bone development 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, SLC13a5 gene expression is found to be upregulated significantly in newly formed rat bone [131] and also at the early stage of osteointegration [132], which is in agreement with the sharply increased accumulation of intraperitoneally injected 14 C labeled citrate in the soft callus after bone fracture [133], pointing out a potential link between citrate biology and bone formation. Moreover, SLC13a5 deficiency could lead to impaired bone formation and defective tooth enamel development [134]. Excitingly, soluble citrate released from citrate-based materials during degradation, after supplemented in osteogenic medium, has been found to elevate the alkaline phosphatase (ALP) of osteoblast-like MG63 cells [72] and to increase the calcium nodule formation of human mesenchymal stem cells (hMSCs) [135].…”
Section: Biology Considerations For Biomaterials Design and Applicationmentioning
confidence: 99%